Evaluation of bonding efficiency between facial silicone and acrylic resin using different bonding agents and surface alterations - Shetty, Uttam Sadashiv (The Korean Academy of Prosthodontics, 2012)
PURPOSE: The aim of the study was to evaluate the effect of 3 silicone primers and 3 surface characterization of acrylic resin surface on bond strength between silicone elastomer and acrylic resin. MATERIALS AND METHODS: 96 Cosmesil silicones bonded to heat-curing acrylic resin were fabricated with the dimension of 75 × 10 × 3 mm. The 3 primers used in this study were G611 platinum primer, A-330 Gold platinum primer, and cyanoacrylates resin. Specimens without primer were used as control. The 3 types of surface characterization done were retentive holes with 1.5 mm in diameter and 0.5 mm deep, retentive beads of 0.6 mm diameter and the third type which was plain without any characterization. The specimens were then checked for bond strength by subjecting them to 180° peel test on a universal testing machine. The obtained results were then subjected to statistical analysis using 2-way ANOVA and Scheffé multiple post hoc procedures. The statistical significance was set at 5% level of significance. RESULTS: The maximum bond strength was seen for samples in which A-330G primer was used followed by G611 primer. The control group showed the minimum bond strength. Surface characterization of retentive holes increased the bond strength considerably as compared to retentive beads and samples without any surface characterization. CONCLUSION: Within the limitations of the study, A-330G primer was more compatible with Cosmesil M511 silicone and has better bonding of Cosmesil to acrylic resin. Retentive holes made on acrylic surface increased the bond strength considerably than those without any surface characterization.